Improvement of Chacha20 Algorithm based on Tent and Chebyshev Chaotic Maps - Taha, Mustafa Hussein; Al-Tuwaijari, Jamal Mustafa (Iraqi Journal of Science, 2021)
Chacha 20 is a stream cypher that is used as lightweight on many CPUs that ‎do not have dedicated AES instructions. As stated by Google, that is the reason why they use it on many ‎devices, such as mobile devices, for authentication in TLS protocol. This paper ‎proposes an improvement of chaha20 stream cypher algorithm based on tent and ‎Chebyshev functions (IChacha20). The main objectives of the proposed IChacha20 ‎algorithm are increasing security layer, designing a robust structure of the IChacha20 ‎to be enabled to resist various types of attacks, implementing the proposed ‎algorithm for encryption of colour images, and transiting it in a secure manner. The ‎ test results proved that the MSE, PSNR, UQI and NCC metrics of ‎IChacha20 are better than those of the original Chacha20. Also, the proposed method has ‎a faster execution time (01:26:4 sec) compared with the original algorithm (02:07:1 sec).